Impact of shading devices on indoor sunlight distribution and building energy performance, with reference to Saudi Arabia - Waheeb, Sahl Abdullah (2006)
Solar shading is one of the cheapest passive cooling techniques employed in hot climates and there is nowadays quite a large number of designs and configurations of shading devices available for architects to use. Considerable work has been done to examine the effect of such shading techniques on space cooling loads. Most published work actually examines the distribution of sunlight on external building surfaces. In regions with both cooling and heating requirements, it becomes important for building designers to understand the impact of solar shading techniques on the thermal performance of buildings throughout the year. There is an obvious need for reducing the exposure of indoor surfaces to direct sunlight in the cooling season but there is also a need to maximise the exposure of such surfaces to direct sunlight for passive heating in the heating season. A search of the literature has shown a clear need for more comprehensive work to produce useful and more specific data relevant to shading techniques and their impact on indoor sunlight distribution, and consequently on cooling and heating loads, throughout the year. This is the main field for the present research which is partially described in this abstract. This work evaluates the performance of different shading techniques using a computer program, “SunCast”, which is a well-known model developed in the UK as part of a large suite of programs. “SunCast” has already been used for more than a decade by many researchers to investigate the solar performance of building components. Initial experiments were conducted to gain confidence in the “SunCast” model by comparing its results against independent, full-scale tests. The research then examines the criteria and techniques that can be used to evaluate the effects of variables like latitude, orientation and other factors on the distribution of sunlight inside a space. A study was carried out later to evaluate the effect of the indoor sunlit area on the resulting cooling and heating loads, and indoor temperature. Part of the thesis discusses a thermal simulation for different shading techniques in different climatic zones. Two climatic regions were selected for the experiments: these were Riyadh, Saudi Arabia, representing a hot climate zone; and London, United Kingdom, representing a cold climate zone. The selection of two climatic zones helps to produce a more useful evaluation of the shading techniques. This evaluation also explains the contribution of the selected shading techniques in reducing or increasing heat gain or loss in both climatic zones in summer and winter. The last part of the thesis presents the main field experiments; these include the physical model and the SunCast model experiments. The experiments were conducted in Jeddah, Saudi Arabia and the efficiency of the selected shading methods were evaluated in this region. The main evaluation reveals that horizontal shading is an efficient shading • method which reduces the internal distribution of the sunlit area. Furthermore, reductions in the sunlit area distribution also reduce the required cooling loads, as revealed by the results. The work which was carried out was as follows: • The variables that affect the sunlit area inside buildings were specified. • Using the IES model, the sunlit area was examined as a quantity and as a percentage using different types of shading device. • Thermal analysis was performed to investigate the contribution of various types of shading device in reducing cooling loads. • A design guide for shading devices in Saudi Arabia was produced.